(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The article examines the importance of variative (optional) programs in preschool educational institutions, as well as the criteria of play-based (movement-based) tests used in monitoring the physical preparedness of children and the indicators applied in their implementation.